Developing a metadata application profile for the daily hire labour - Sen, Sangeeta (2018)
This work has been developed under the “EMPOWER SSE: A Linked Open Data Framework for the Empowerment of Social and Solidarity Economy Agents” project, in the scope of the Indoportugal Intergovernmental Programme of Cooperation in Science and Technology. Department of Science & Technology (DST, India). Ref No. DST/INTPORTUGAL/P- 06/2017 This work has been partially supported by COMPETE: POCI-01-0145-FEDER-007043 and FCT – Fundação para a Ciência e Tecnologia within the Project Scope: UID/CEC/00319/2013.